Bilaterality of drusen. Issue 3 (March 1990) - Barondes, M; Pauleikhoff, D; Chisholm, I C; Minassian, D; Bird, A C
Abstract : The characteristics of drusen in 81 patients with bilateral drusen as a manifestation of age related disease were analysed for symmetry between the two eyes. It was found that there was close concordance with respect to drusen size, number, density, and fluorescence which was greater than would have been expected by chance alone. This finding implies that drusen may result from metabolic malfunction specific to the patient rather than the non-specific result of aging.